Serological Diagnosis of Brucella Infection in Cetaceans by Rapid Serum Agglutination Test and Competitive ELISA with Brucella abortus and Brucella ceti as Antigens - Tiziana Di Febo; Gabriella Di Francesco; Carla Grattarola; Luigina Sonsini; Ludovica Di Renzo; Giuseppe Lucifora; Roberto Puleio; Cristina Esmeralda Di Francesco; Camilla Smoglica; Giovanni Di Guardo; Manuela Tittarelli (Pathogens)
Rose Bengal antigen and smooth lipopolysaccharide (s-LPS) were produced from a field strain of Brucella ceti (“homologous” antigens) and from the reference strain B. abortus S99 (“heterologous” antigens); they are currently used for the diagnosis of brucellosis in cattle, water buffaloes, sheep, goats, and pigs, as recommended in the Manual of Diagnostic Tests and Vaccines for Terrestrial Animals of the World Organization for Animal Health (WOAH). “Homologous” and “heterologous” antigens were used in a rapid serum agglutination test (Rose Bengal test, RBT) and a competitive ELISA assay (c-ELISA) to test a panel of sera, blood, and other body fluids (cerebrospinal fluid, pericardial fluid, tracheal fluid, and aqueous humor) collected from 71 individuals belonging to five cetacean species (Stenella coeruleoalba; Tursiops truncatus; Grampus griseus; Globicephala melas; and Ziphius cavirostris), which were found stranded on the Italian coastline. Six animals were positive for Brucella spp. for bacterial isolation and/or PCR, and 55 animals were negative; for the remaining 10 animals, no PCR/isolation data were available. A total of 90 samples were tested. Results obtained from the two tests were compared in order to identify the most suitable antigen for the serological diagnosis of Brucella infection in cetaceans. The RBT performed with the “homologous” antigen showed the best results in comparison with the “heterologous” antigen: diagnostic sensitivity, specificity, and accuracy were 80.0%, 44.1%, and 46.9% for the “homologous” antigen and 80.0%, 17.0%, and 21.9% for the “heterologous” antigen. For the c-ELISA, “homologous” and “heterologous” s-LPS showed similar results (diagnostic sensitivity 66.7%, diagnostic specificity 97.3%, and diagnostic accuracy 95.0%). Therefore, the RBT using the “homologous” antigen and c-ELISA with “homologous” or “heterologous” s-LPS could be used in parallel for the detection of antibodies against Brucella spp. in cetaceans.